Integrasi Sosial Masyarakat Multietnik Di Nagari Sitiung Kabupaten Dhamasraya - Retno Anggraini (Jurnal Sosiologi Andalas, 2019)
The transmigration program is one of the causes of the multi-ethnic communities in a place, becausein addition to the presence of different ethnic groups being moved to the area, it also invites the arrival of otherethnic groups from various places as a result of new economic developments in the direction of transmigrationdestinations. In many places in Indonesia there are conflicts between indigenous people and ethnic migrants. Incontrast to Nagari Sitiung, with the village bedol transmigration program since 1976 there are people withvarious ethnicities with dominant ethnic groups Minangkabau and Javanese, creating a harmonious life in thecommunity. So it is interesting to be researched how the functioning of social institutions in the communitycreates a harmonious life. The purpose of this study is 1) to analyze the workings of multi-ethnic communitysocial institutions, so that harmonious social integration takes place, 2) Describe the forms of social integrationof multi-ethnic societies, so as to support harmonious social life. As a knife for analyzing this research, thetheory rational choice was used by James Coleman. This research methodology uses a qualitative approach, whilethe type of research used is descriptive. Selection of informants by using purposive sampling. Data collection isdone by using observation techniques and in-depth interviews. The research results show that social integrationof the community occurs by the work of social institutions in the community that can integrate the community,especially the two dominant ethnic groups (Javanese and Minangkabau). Social institutions that work includemarriage and family institutions, political institutions, educational institutions, religious institutions, economicinstitutions. Forms of cooperation between ethnic groups supporting social integration are collaboration carriedout by the multi-ethnic community, such as in educational activities, the implementation of traditionalceremonies, religious ceremonies, mutual cooperation in various development activities and decision making inNagari Sitiung.